2020
DOI: 10.1016/j.jvscit.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of an abdominal aortic aneurysm associated with crossed fused renal ectopia

Abstract: Chimney/snorkel endovascular aneurysm repair (Ch-EVAR) enables the minimally invasive treatment of abdominal aortic aneurysm in anatomically challenging and high-risk surgical cases. Here, we present the case of a 77-year-old man with an abdominal aortic aneurysm associated with crossed fused renal ectopia and an ectopic renal artery arising directly from the aneurysm sac. After successful implementation of Ch-EVAR, computed tomography angiography at 18 months revealed no endoleaks, patency of the parallel gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the literature, there are case reports showing the technical aspects of the endovascular treatment of abdominal aortic aneurysm in patients with renal ectopia [14,15,16]. Tsuboi et al [17] reported a case of partial nephrectomy in patients with left-to-right crossed fused renal ectopia with clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are case reports showing the technical aspects of the endovascular treatment of abdominal aortic aneurysm in patients with renal ectopia [14,15,16]. Tsuboi et al [17] reported a case of partial nephrectomy in patients with left-to-right crossed fused renal ectopia with clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] and Colacchio et al . [ 10 ] placed self-expanding endografts (Viabahn Endoprosthesis, LG GORE, Delaware, USA) into RAs that arose from the AAA sacs in their cases. Here, we opted for the reversed chimney graft technique using Viabahn VBX, a balloon-expanding endograft.…”
Section: Discussionmentioning
confidence: 99%